Death of an Irish diva - Bryan, Mollie Cox, 1963- (Bryan, Mollie Cox, 1963- Cumberland Creek mystery., 2014)
When famed Irish dancer Emily McGlashen is found murdered in her studio just after the St. Patrick's Day parade, one of the Cumberland Creek Scrapbook Crop becomes a prime suspect.